Filling the language gap: the feasibility of communication resources used in the provision of healthcare for HIV/AIDS and tuberculosis in the Eastern Cape, South Africa - Von Witt, Nathalia Jane (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
South Africa has the largest number of Human Immunodeficiency Virus (HIV)-positive people in the world, the third-highest rate of Tuberculosis (TB) infections, and the second-highest rate of Multi-Drug Resistant TB (MDR-TB) globally, with up to 60% of HIV-positive healthcare users (HCUs) infected with TB as a co-infection. Both HIV/AIDS and TB require strict medicines adherence for disease management or treatment respectively; however, this is often not attained, and as such these statistics also represent lives affected by or lives lost to these diseases. Moreover, in South Africa, up to 80% of healthcare consultations are conducted through a second language. Despite language policies suggesting the contrary, African languages are neglected in healthcare provision in South Africa. This perpetuates inequalities within the South African healthcare system by limiting HCUs understanding of and agency in their own healthcare and maintaining a barrier to more effective treatment. Such language barriers may also result in HCUs defaulting on treatment. Added to this, the fear and mistrust arising from language power dynamics contributes to high rates of avoidance behaviour. This research therefore aimed to (a) explore how healthcare professionals (HCPs) and HCUs communicate when they are not fluent in the same language in care for HIV/AIDS and TB patients; (b) develop practical and feasible strategies that would enable HCPs to address language barriers in their consultations for HIV and TB and (c) to empirically evaluate these strategies in a pilot feasibility trial in the Eastern Cape. The first aim (a) concerning the problem of language barriers in healthcare consultations was addressed through identifying communication barriers experienced by HCPs in South Africa, exploring the strategies used to navigate or alleviate these barriers, creating and implementing communication resources, and analysing the effects of these resources on HCPs' communication. A selective narrative review was conducted (Chapter 2) to identify the main communication problems experienced by HCPs and HCUs, as well as the main communication strategies and resources used by HCPs to reduce these communication problems. This was further explored by conducting two needs analyses with HCPs (n=31) in South Africa, and specifically in the Eastern Cape, which revealed differing perspectives on health communication and confirmed HCPs' need for communication resources. For the second aim (b), existing communication resources were reviewed and selected or further developed following a Participatory Action Research approach, and then (c) empirically evaluated in a pilot feasibility trial with six healthcare sites in the Eastern Cape. Both the needs analyses and the pilot feasibility trial were adapted to employ an online or blended approach due to COVID-19-related limitations. The feasibility and acceptability of both the study protocol and the proposed communication resources were evaluated. Three major findings emerged from this research. First, this research echoed existing literature confirming that HCPs do not have the support they need at a structural level. Second, while it was found that there is no one-size-fits-all solution for resources and training to improve HCP-HCU communication, it was noted that the most appropriate resources are those that are flexible, and those that support HCPs' language learning. HCPs who were already sensitive to communication barriers and were already taking steps to improve their second language (L2) proficiency also took initiative to use the resources in ways other than those suggested in order to best support the communication needs of them and the HCUs they consulted. Third, and linked to the second finding, it was found that communication resources that covered conditions including, but not limited to, HIV and TB were more appropriate. HCPs who used the resources showed a small, although not statistically significant, increase in communication satisfaction, satisfaction with resource support, and trust after using the resources for one month. Although implementation problems were encountered in some settings of the intervention, it was found that this intervention has the potential to be further evaluated in a larger, multi-site randomised controlled trial (RCT). These findings inform recommendations which are made to improve the feasibility of such a study in order to conduct an RCT; to further develop the resources in order to enhance communication between HCPs and HCUs both in HIV and TB consultations and in other fields of healthcare; and to implement a similar intervention at the university level and as Continuing Medical Education. The insights gained into HCPs' support for language support resources, which resources were used, and particularly how they were used, are significant for taking actionable steps in supporting HCPs' provision of more equitable healthcare in multilingual South Africa.
Keywords: Communication in community health services -- South Africa -- Eastern Cape; Language and languages -- South Africa -- Eastern Cape; Multilingualism; Medical care -- South Africa; Communication in public health; Health literacy